2019
DOI: 10.1029/2018jg004707
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Regulates the Activity, Community Structure, and Functional Potential of Heterotrophic Bacterioplankton in an Oligotrophic Gyre

Abstract: Ocean acidification (OA), a consequence of increased global carbon dioxide (CO 2 ) emissions, is considered a major threat to marine ecosystems. Its effects on bacterioplankton activity, diversity, and community composition have received considerable attention. However, the direct impact of OA on heterotrophic bacterioplankton is often masked by the significant response of phytoplankton due to the close coupling of heterotrophic bacterioplankton and autotrophs. Here we investigated the responses of a heterotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Though a dearth of information is available on interactions among marine bacterial assemblages under elevated temperature conditions, several reports describing the potential impact of other environmental anomalies such as ocean acidification (reduction in seawater pH) are available. For example, alterations in microbial ecological networks under elevated CO 2 condition has been observed by Xia et al 72 . Nevertheless, this is not always the case, as few studies have also found that microbial intra-species interactions among marine microorganisms are either less affected or unaffected in climatic changes such as elevated partial pressure of CO 2 ( p CO2) 73 .…”
Section: Discussionmentioning
confidence: 89%
“…Though a dearth of information is available on interactions among marine bacterial assemblages under elevated temperature conditions, several reports describing the potential impact of other environmental anomalies such as ocean acidification (reduction in seawater pH) are available. For example, alterations in microbial ecological networks under elevated CO 2 condition has been observed by Xia et al 72 . Nevertheless, this is not always the case, as few studies have also found that microbial intra-species interactions among marine microorganisms are either less affected or unaffected in climatic changes such as elevated partial pressure of CO 2 ( p CO2) 73 .…”
Section: Discussionmentioning
confidence: 89%
“…The relative abundance of Alteromonadaceae and SAR86 increased under OA. Alteromonadaceae with relatively large cell size and the ability to thrive in nutrientdeficient situations (Lopez-Perez and Rodriguez-Valera, 2014) is repressed by ocean acidification (Xia et al, 2019). The different response of Alteromonadaceae to OA might result from the different environmental conditions, as Xia's experiment is conducted during a heterotrophic bloom phase, in which BP is 20-40 folds higher than at M8.…”
Section: Effect Of Ocean Acidification On Bacterial Community Composimentioning
confidence: 99%
“…Westwood et al (2018) report that an increase in BP is attributed to the effect of OA on phytoplanktonderived DOC and the lower grazing pressure in highly productive waters. Xia et al (2019) suggest that enhanced BP under high pCO 2 is caused by the physiological adjustment of bacterial cells. Instead, in mesopelagic regions, high pCO 2 reduces BP in Hawaiian deep seawater (Coffin et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that responses of bacterioplankton communities to elevated pCO 2 are diverse and complex and even conflicting. Bacterioplankton communities were found to be susceptible to changes in pCO 2 or pH in some studies that were reflected in abundance, diversity, or composition (Krause et al, 2012;Zhang et al, 2013;Xia et al, 2019;Aguayo et al, 2020;Crummett, 2020), whereas other studies reported negligible effects (Roy et al, 2013;Oliver et al, 2014;Wang et al, 2015). Take coastal ecosystems for example, microbial community from coastal ecosystem with naturally low pH (average = 7.8) was still sensitive to acidification (Crummett, 2020).…”
Section: Introductionmentioning
confidence: 99%